Busy. Please wait.
or

Forgot Password?

Don't have an account?  Sign up
or

taken

why

Make sure to remember your password. If you forget it there is no way for StudyStack to send you a reset link. You would need to create a new account.

By signing up, I agree to StudyStack's Terms of Service and Privacy Policy.

Already a StudyStack user? Log In

Reset Password
Enter the email address associated with your account, and we'll email you a link to reset your password.

Remove ads
Don't know (0)
Know (0)
remaining cards (0)
Save
0:01

 Flashcards Matching Hangman Crossword Type In Quiz Test StudyStack Study Table Bug Match Hungry Bug Unscramble Chopped Targets

Embed Code - If you would like this activity on your web page, copy the script below and paste it into your web page.

Normal Size     Small Size show me how

# Complex Numbers

QuestionAnswer
What is the square root of negative 36? √-36 √-36 = √36 x √-1 = 6 x i = 6i
How about the negative square root of negative 36? -√-36 -√-36 = -(√36 x √-1) = -6 x i = -6i
Solve this equation (7 + 2i) + (2 + 4i) (7 + 2i) + (2 + 4i) = (7 + 2) + (2 + 4)i = 9 + 6i
Now we’ll try the same problem with a negative i (7 - 2i) + (2 + 4i) (7 - 2i) + (2 + 4i) = (7 + 2) + (-2 + 4)i = 9 + 4i
Subtraction is just as easy (7 + 4i) - (2 + 2i) (7 + 2i) - (2 + 4i) = (7 - 2) + (2 - 4)i = 5 - 2i
Don’t be fooled if there isn’t a second real number (7 + 2i) - (4i) (7 + 2i) - (4i) = (7 - 0) + (- 4)i = 7 - 2i
When multiplying complex numbers remember that the product rule for radicals doesn’t apply √-36 x √-49 √-36 x √-49 = 6i x 7i = 42i2 = 42(-1) = -42
Here’s another multiplication example 6i(2 - 7i) 6i(2 - 7i) = 12i – 42i2 = 12i – 42(-1) = 12i + 42 = 42 + 12i
Remember the FOIL method? (2 - 7i)(4 + 3i) (2 - 7i)(4 + 3i) = 8 + 6i - 28i – 21i2 = 8 – 22i - 21i2 = 8 – 22i - 21(-1) = 8 – 22i + 21 = 29 – 22i
Conjugate is hard to say but we need it for division 2 + 4i / 3 – 6i 2 + 4i / 3 – 6i = (2 + 4i x 3 + 6i) / (3 – 6i x 3 + 6i) = 6 + 12i + 12i + 24i2 / 9 + 18i – 18i – 36i2 = 6 + 24i + 24(-1) / 9 – 36(-1) = (-18 + 24i) / 45 = - 18/45 + 24i / 45
Created by: csmatthews